A Critical Discourse Analysis on Instagram @Sajak Maluku based on the Van Dijk’s model - Marce Laimena; Smarty Jabez Samuel Satumalay; Stella Rose Que (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
This research discusses critical discourse analysis based on Van Dijk's theory on the Instagram account of @Sajak_Maluku. It aims to explain the theme and moral lessons embedded in the discourse on the Instagram account of @Sajak_Maluku. This was descriptive qualitative research. The data source in this research was the Instagram account of @Sajak_Maluku. The technique of data collection was done by documenting the screenshots of the images containing the discourse on the @Sajak_Maluku Instagram account. Furthermore, the discourse was analyzed using the critical discourse analysis method with a content analysis model based on Van Dijk's theory. The critical discourse analysis method was carried out to explain the hidden purpose in the discourse, while content analysis aims to explain the content of the discourse. The results of this research show that there are two themes in the discourse on the @Sajak_Maluku Instagram account from June 1 until June 10, 2022, which are self-reflection and religious themes. Moral values which can be concluded from religious themes are how we have to be thankful for our everyday life, and we have to keep praying for everything from self-reflection theme is advice to ourselves in relation to what we face every day.